The immune reconstitution inflammatory syndrome after antiretroviral therapy initiation in patients with tuberculosis: findings from the SAPiT trial. - Naidoo, Kogieleum; Yende-Zuma, Nonhlanhla; Padayatchi, Nesri; Naidoo, Kasavan; Jithoo, Niraksha; Nair, Gonasagrie; Bamber, Sheila; Gengiah, Santhana; El-Sadr, Wafaa M; Friedland, Gerald; Karim, Salim Abdool (Annals of internal medicine, 2012)
Concerns about the immune reconstitution inflammatory syndrome (IRIS) remain a barrier to antiretroviral therapy (ART) initiation during antituberculosis treatment in co-infected patients.
Keywords: Adult; AIDS-Related Opportunistic Infections; Anti-Retroviral Agents; Antibiotics, Antitubercular; CD4 Lymphocyte Count; Female; HIV Infections; Humans; Immune Reconstitution Inflammatory Syndrome; Immunocompromised Host; Incidence; Kaplan-Meier Estimate; Male; Prospective Studies; Rifampin; Risk Factors; Severity of Illness Index; Tuberculosis